Person–Job Misfit: Perceived Overqualification and Counterproductive Work Behavior - Khan, Jawad; Ali, Amna; Saeed, Imran; Vega-Muñoz, Alejandro; Contreras-Barraza, Nicolás (Frontiers in Psychology, 2022)
Perceived overqualification and counterproductive work behaviour were examined in this study by identifying job boredom as a mediator and job crafting as a moderator. Hierarchical regression analysis and Hayes' PROCESS macro method were used to assess hypotheses in a three-wave survey of 317 textile sector employees. The findings show that perceived overqualification is positively related with counterproductive work behaviour caused by job boredom. Furthermore, the findings suggest that job crafting moderates the positive connection between perceived overqualification and job boredom and the indirect connection between perceived overqualification and counterproductive work behaviour via job boredom. The model was tested using 3-wave data; however, since the data were attained from a single source, questions of common method bias cannot be ruled out. Managers should look for changes in employee attitudes and promptly modify employees' positions when they indicate that they have more experience, abilities, and talents required for their roles in their organisations. Integrating person-job fit theory, this study adds to the growing literature on perceived overqualification. This study further examined the mediating function of job boredom and the moderating impact of job crafting in the association between perceived overqualification and counterproductive work behavior.